Pain and limitations of mouth opening: a case report: Nyeri dan keterbatasan membuka mulut: sebuah laporan kasus - Muhammad Iswanto Sabirin; Eri Hendra Jubhari; Ian Afifah Sudarman (Makassar Dental Journal, 2022)
Temporomandibular joint disorders (TMD) do not always indicate a problem in the joints but also involve all disorders related to the function of the masticatorysystem. One of the common signs of TMD is pain and limitations of mouth opening. When a pa-tient has a joint disorder and a masticatory muscle disordersimultaneously and the primary diagnosis cannot be determined, it is generally agreed to treat the masticatory muscle disorder as the primary diagnosis. Thereforethe initial treatment is directed to-wards the muscular symptoms. If symptoms do not decrease, further therapy is required for the joint disorder. This article re-ports on muscles therapy and the use of occlusal splints to rehabilitate pain and limitations of mouth opening. A 16-year-old female came to ProsthodonticDepartment RSGM Unhas, with complaints of pain when opening and closing her mouth. The pain and sound of crack on the right side of the face were felt for a few minutes since 2 months ago. The patient chews fre-quently in the left region because of caries and pain in the maxillary right molar since 2 months ago.Tooth 36 was extracted about 1 year ago due to residual roots. It was concluded that muscles therapy and occlusal splints are effectively overcome the limitations of mouth opening and reduce pain in the jaw joint.